174k views
2 votes
Simplify surd need an answer asap please

Simplify surd need an answer asap please-example-1

1 Answer

8 votes

Answer:

Explanation:

Simplify Surd:

  • Multiply the denominator and numerator with the conjugate of the denominator.
  • Conjugate of denominator:


\sf (√(x+1)) + (√(x-1))


\sf(√(x+1) +√(x-1))/(√(x+1)-√(x-1)) = ((√(x+1) +√(x-1))(√(x+1) +√(x-1)))/((√(x+1) -√(x-1))(√(x+1) +√(x-1)))\\

When doing so, in the numerator, we get in the form of the identity (a +b)² and in the denominator a² - b²


\sf =((√(x+1) +√(x-1))^2)/((√(x+1))^2 - (√(x-1))^2)\\\\=((√(x+1))^2+(√(x-1))^2+2*√(x+1)*√(x-1))/(x + 1 - (x - 1))\\\\=(x+1 +x -1 + 2*√((x+1)(x-1)))/(x + 1 - x + 1)\\\\=(x+ x + 1 - 1 +2√(x^2-y^2))/(x-x+1+1)\\\\=(2x+2√(x^2-y^2))/(2)\\\\= (2x)/(2)+(2√(x^2-y^2))/(2)\\\\=x + √(x^2-y^2)

User SingerOfTheFall
by
4.9k points